Hydromechanical couplings of reinforced tensioned members of steel fiber reinforced concrete by dual lattice model. (28th September 2020) - Pham, Duc Tho; Sorelli, Luca; Fafard, Mario; Vu, Minh‐Ngoc
Abstract: The durability of concrete structures strongly depends on the water and chloride penetration in cracked concrete during its service life. This work aims at modeling the damage effect of tension stiffening behavior on the permeability for concrete tie specimen under tensile load by a dual lattice model, which considers hydromechanical couplings. Three concrete materials, including normal strength concrete (NSC), steel fiber reinforced concretes (SFRC), and ultra high‐performance fiber reinforced concrete (UHPFRC), are considered. The hydromechanical lattice model is based on a dual element network modeling: the water transport and the mechanical response. The fiber bridging effect is considered by means of the cohesive law of Mazars. The water flow in the damaged conduit elements is proportional to the cube of the crack width, which results from the damage variable. Experimental results available in open literature for both NSC and SFRC tie specimens are used to analyze and validate the proposed model. Considering a UHPFRC tie specimen, the model well predicted the load drops due to macrocrack occurrence, load hardening, and permeability evolution. Based on the present results, the current lattice hydromechanical model is a useful tool for predicting the service life of steel bar reinforcing concrete structure with and without steel fiber reinforcement.